Frontofacionasal Dysplasia in a Newborn with a De Novo Duplication of 7p15.2-p15.1 - Tamer Mansour; Sainan Wei; Michael Netzloff; Tarek Mohamed; Brian Schutte; Said A. Omar (Thieme Medical Publishers, Inc., 2015)
Abstract We report a new case of frontofacionasal dysplasia or dysostosis (FFND) with a 1.5 Mb duplication in the region of 7p15.2-p15.1, and provide a review of the literature to understand the underlying pathogenesis better.